Investigating Family Vulnerability, Financial Attitudes and Debt Behavior of Bank Emok Borrowers - Rima Syifani Fuadah; Euis Sunarti; Syifa Istighfarani (Journal of Consumer Sciences, 2024)
Bank Emok continues to be a significant part of family finances despite the high-interest burden associated with it. Bank Emok is an informal financial institution in Indonesia that provides money-lending services to the community by traveling or visiting customers directly. This study analyzes the influence of family vulnerability and financial attitudes on debt behaviors among families who are customers of Bank Emok. Conducted as a cross-sectional study with a sample of 150 wives selected through simple random sampling in the Tanah Sereal Sub-district of Bogor City, results show that almost half of the families exhibit low family vulnerability, low financial attitudes, and moderate debt behavior. Family vulnerability shows significant difference between poor and non-poor families according to 1.5x Bogor City’s and World Bank’s Poverty Line 2022. Regression tests showed that financial attitudes, length of husband's education, per capita income, and attendance mechanisms had a significant positive effect on debt behavior. In conclusion, to decrease family vulnerability and increase financial attitudes toward debt behavior, it is important for families to improve their financial attitudes and manage household financial skills through financial management training conducted at each meeting.